The Impact of Parents’ Educational Level and Students’ Gender on Students’ Science Academic Achievement in Four Southeast Asian Countries - Quang-Vinh Trinh (Journal of Basic Education Research, 2020)
Purpose of study: This paper aims at exploring the factors that affect the science academic achievement of Indonesia, Singapore, Thailand, and Vietnam students by using the PISA 2015 dataset. Methodology: This paper uses a data mining method to explore the PISA 2015 data to answer the research questions and achieve the research aims. The targeted students were selected from ASEAN countries, including Indonesia, Singapore, Thailand, and Vietnam. The total number of samples was 26,703 students and their age ranged from 15.3 to 16.2. Min finding: The results of this paper indicate parents’ educational level and students’ gender create significant differences in students’ science academic achievement in four Southeast Asian countries. Novelty/Originality of this study: The paper intends to explore significant differences in the students’ science academic achievement, between parents’ educational level and students’ gender in four Southeast Asian countries.